EFFECT OF MARKETING MIX DECISIONS TO PURCHASE HONDA BEAT MOTORCYCLE (CASE STUDY IN CV. HAYATI PADANG) - Fitri Yeni, Wiza; Yolanda Utami, Hayu; Amaluis, Dina (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to determine the effect of product, price, promotion and distribution of the purchasing decisions in the CV. Hayati Padang. Where the independent variable is the product (X1), price (X2), promotion (X3), and distribution (X4) influence the purchase decision (Y) as the dependent variable. The population in this study is that consumers CV. Hayati Padang. Samples were taken as many as 100 respondents using a technique nonprobality sampling (non-probability sampling). Data was collected using a survey method through questionnaires filled out by consumers. Then the data were analyzed using multiple linear regression analysis. This analysis includes Validity Test, Reliability Test, Regression Analysis, Test Classical Assumptions, Hypothesis Testing through F test and t test, and analysis of the coefficient of determination (R²). Based on the research results, obtained by the regression equation: Y = 6,623 + 0.247 X1 - 0.273 X2 + X3 + 0.376 X4 0494. Based on statistical data analysis, the indicators in this study are valid and variables are reliable. In the classical assumption test, normal distribution, does not occur heterosdastisitas, regression models multikolonieritas free and linearity test revealed a linear form. Individually, the variables that have the most impact is the variable distribution of the regression coefficient of 0.494, followed by promotion variables with regression coefficient 0.376, then 0.273 and the final price is variable products with regression coefficient 0.247. Hypothesis testing using t-test showed that the variables of product, price, promotion and distribution is found to significantly affect the dependent variable purchase decision. Then through the F test can be seen that the independent variables to test the dependent variable worth purchasing decisions. Figures Adjusted R Square of 0.871 or 87.1 units indicates that the variable purchase decisions can be explained by the variable product, promotion, price and distribution, while the rest of 12.9 units is explained by other variables that are not used in this study.